Ide pemanfatan ruang bawah tangga : Solusi untuk rumah bertingkat di lahan terbatas / Andie A. Wicaksono, M. Zaka Helematyar, Azzam zulfikar ; editor Luthfi Kurniawan - ANDIE A. WICAKSONO; Zaka Helematyar; Azzam Zulfikar; Luthfi Kurniawan (Griya Kreasi, 2015)
139 hlm : ilus ; 22 cm [3 eks]